Risks and financing decisions: dynamic panel data evidence from the Philippines - Chow, Yee Peng; Muhammad, Junaina; Amin Noordin, Bany Ariffin; Cheng, Fan Fah (Panoply Consultancy, 2017)
Using a sample of listed non-financial Philippine firms over the period 2004-2014, this study empirically examines the effects of macroeconomic and firm-specific uncertainty on firm leverage. We employ a dynamic panel data method, namely the robust two-step system GMM estimator on both the book and market leverage ratios. We further analyze the effects of macroeconomic and firm-specific uncertainty on firm debt maturity. The results provide strong evidence of the negative effects of macroeconomic and firm-specific uncertainty on firm leverage. The results also indicate that while short-term debt is adversely affected by both firm-specific and macroeconomic uncertainty, long-term debt is only affected by macroeconomic uncertainty. This implies that although the Philippine firms take into account both firm-specific and macroeconomic uncertainty in their financing decisions in the short-run, they are only concerned about the adverse effects of macroeconomic uncertainty in the long-run.